Without arrows [videorecording (DVD)] - Fiddler, Delwin Elk Bear (First Run Features, 2025)
"The poignant feature documentary 'Without Arrows' chronicles three generations of a Lakota family as Delwin Fiddler Jr., an acclaimed grass dancer, returns to his ancestral home on the Cheyenne River Sioux Tribe Reservation in South Dakota. After 11 years of living in Philadelphia, he leaves his big city life behind, aiming to reconnect with his mother and father and learn more about their family history. A portrait of the Fiddlers, 'Without Arrows' begins as Delwin works to rebuild his life and sense of identity while navigating within his family and within the larger culture of the reservation. Delwin experiences struggles and frustrations as he attempts to rekindle an interest in traditional Lakota lifeways while healing from the trauma that caused him to leave home in the first place. Through tenderness and tragedy Without Arrows celebrates the emotional arcs and hidden longings of the Fiddler family as they strive to carry on the legacy of their ancestors to the next generation." --